"Propuesta de guía para la administración efectiva de proyectos durante el inicio de operación de nuevas obras de infraestructura hospitalaria de la CCSS en el área mecánica." - Gutiérrez-Vásquez, José Alberto; Sánchez-Acevedo, Gerald (Instituto Tecnológico de Costa Rica, 2011)
This March 2011 Bulletin issued by the Quality Committee of the Direction of Project Management (DAPE in Spanish), touches upon the innovative mixture used in this department of the CCSS, among the concepts issued by the ISO 9001-2001 norm, utilized for the development of the Project Quality Management System (SGCP in Spanish) and the implementation of projects according to the guidelines provided in the Project Management Body of Knowledge Guide (PMBOK) of the Project Management Institute (PMI). In recognizing the use of the ISO 9001-2001 norm as the basis of its Quality Management System, used in a compulsory manner by all its members, the DAPE aims at reaching a competitive advantage with regard to other units of the Caja Costarricense de Seguro Social, and enabling its participation in a certification process. Consequently, as a general objective the DAPE is proposing to prepare a Guide for Effective Project Management during one of the four phases that are comprised in a Project at the CCSS, the Transitional Phase. This document encompasses necessary techniques and tools (mainly focusing at the mechanical engineering branch) to set out a normalized methodology in the DAPE during the period between the transition to the closing of the Investment in Building Phase and the beginning of the Operational Phase, until the Accepted Receipt of the outcome by the client.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, Escuela de Ingeniería en Computación, Escuela de Ingeniería en Construcción, 2011.
Keywords: Derecho constitucional; Costos; Metodología; Valores; Comunicación organizacional